Deep Correlated Metric Learning for Sketch-based 3D Shape Retrieval - Dai, Guoxian; Xie, Jin; Zhu, Fan; Fang, Yi (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
The explosive growth of 3D models has led to the pressing demand for an efficient searching system. Traditional model-based search is usually not convenient, since people don't always have 3D model available by side. The sketch-based 3D shape retrieval is a promising candidate due to its simpleness and efficiency. The main challenge for sketch-based 3D shape retrieval is the discrepancy across different domains. In the paper, we propose a novel deep correlated metric learning (DCML) method to mitigate the discrepancy between sketch and 3D shape domains. The proposed DCML trains two distinct deep neural networks (one for each domain) jointly with one loss, which learns two deep nonlinear transformations to map features from both domains into a nonlinear feature space. The proposed loss, including discriminative loss and correlation loss, aims to increase the discrimination of features within each domain as well as the correlation between different domains. In the transfered space, the discriminative loss minimizes the intra-class distance of the deep transformed features and maximizes the inter-class distance of the deep transformed features at least a predefined margin within each domain, while the correlation loss focuses on minimizing the distribution discrepancy across different domains. Our proposed method is evaluated on SHREC 2013 and 2014 benchmarks, and the experimental results demonstrate the superiority of our proposed method over the state-of-the-art methods.